Effect of post-weld heat treatment on the microstructure and mechanical properties of copper-steel joints of silver-based composite filler metals. (March 2023) - Shi, Yinkai; Yu, Hua; Wei, Shizhong; Long, Weimin; Li, Yunpeng; Zhang, Liangliang; Cao, Xinna; Huang, Lingling; Song, Luyang; Yu, Zhuoli; Zhong, Sujuan; Jiu, Yongtao; et al.
Abstract: The purpose of this article was to provide a theoretical basis for the manufacture and practical working application of metal composite plates by simulating the law of influence on the interfacial characteristics, microstructure, composition and mechanical properties of copper/steel composite plates after post-weld heat treatment under working conditions. In this study, the microstructure and melting properties of BAg30T filler metal were investigated. The effect of heat treatment on the microstructure and mechanical properties of brazing joints in Cu-Fe dissimilar metal joints was investigated using field-emission scanning electron microscopy (SEM-EDS), electron backscattering diffraction (EBSD), a microindenter, and universal tensile testing machine. The results indicated that the microstructure of the filler metal consisted of an Ag-based solid solution (Ag(s.s)) and a Cu-based solid solution (Cu(s.s)). With the simultaneous increase in temperature and rapid cooling method, the brazing seam developed a (Ag+ Cu) eutectic phase in addition to Ag(s.s) and Cu(s.s). The grain sizes, texture strengths, orientation angle distributions, and plastic deformations of Ag(s.s) and Cu(s.s) in the joints were significantly changed. The microhardness of Cu(s.s) was greater than that of Ag(s.s). The tensile strength of the Cu-Fe joint obtained through the PWHT process at 600 °C reached a peak of 216 MPa, indicating that a change in the PWHT process can improve the mechanical properties of the brazed joint. The fracture form of the brazed joints changed from the initial fracture along the crystal to mixed fracture. Graphical Abstract: ga1 Highlights: In this study, the microstructure and melting properties of BAg30T filler metal were investigated. The microstructure of brazed joints was investigated under different post-weld heat treatment processes. Coarsening behavior and texture formation mechanism of Ag-based solid solution and Cu-based solid solution are analyzed. Effect of grain boundary characteristic distribution and susceptibility to reheat defects are analyzed. Influence of post-weld heat treatment processes on mechanical properties of brazed joints are analyzed.